Microalgal Polyphosphate Drives One-Pot Complete Enzymatic Generation of Flavin Adenine Dinucleotide from Adenosine and Riboflavin - Sung, Yi-Jung; Takahashi, Takumi; Lin, Yi-Hsuan; Jia, Tony Z.; Chiang, Yin-Ru; Wang, Po-Hsiang (ACS Sustainable Chemistry & Engineering, 2024)
Flavin adenine dinucleotide (FAD) is a universal cellular cofactor involved in biological redox and radical metabolism reactions. FAD biosynthesis from riboflavin typically proceeds through two ATP-dependent enzymatic reactions, with flavin mononucleotide (FMN) as the intermediate. Traditional in vivo methods employ microorganisms for FAD synthesis at an industrial scale; however, these approaches often suffer from complex purification processes. Considering the atomic economy and percentage yield, in vitro enzymatic FAD synthesis using enzymes could be a more efficient and sustainable alternative. While catalytically efficient, the requirements of expensive ATP (substrate) limit the industrialization of enzymatic FAD synthesis. To overcome the ATP requirements, here we develop a two-enzyme cascade for ATP regeneration from adenosine using wastewater microalgal polyphosphate as the P-donor. With the ATP regeneration system, the bifunctional riboflavin kinase/FAD synthetase and pyrophosphatase completely convert saturated riboflavin into FAD within 2 h with a titer of ∼1.2 g/L (1.5 mmol/L). Notably, orthophosphate, the only byproduct of this enzymatic process, can be recycled to synthesize polyphosphate by wastewater microalgae, which can then be fed back into the system as the P-donor in the ATP regeneration step, resulting in a FAD synthesis process with almost net-zero waste generation.